MOBILE BANKING SERVICES AND FINANCIAL INCLUSION AMONG SMALL SCALE FARMERS IN RURAL AREAS: A CASE OF NAKISUNGA SUB-COUNTY, MUKONO DISTRICT - Precious Kasemiire (Uganda Christian University, 2024)
The study sought to investigate the impact of mobile banking on financial inclusion in rural areas of Uganda, with a specific focus on small scale farmers in Katente Village, Nakisunga sub-county Mukono District. The study was guided by three objectives: examining the relationship between mobile payments service and financial inclusion among small scale farmers, establishing the relationship between mobile savings service and financial inclusion among small scale farmers and finding out the relationship between mobile loans service and financial inclusion among small scale farmers in Nakisunga. The study was carried out using cross-sectional research design where quantitative research approach was utilized. Simple random sampling method was used to get a sample of 36 respondents who were small scale farmers in Katente village, Nakisunga Sub-County, Mukono district and these responded to the questionnaires that were used to collect data. From the study findings, it was revealed that mobile payment, mobile savings, and mobile loan services each significantly enhance financial inclusion among small-scale farmers in Katente Village, with positive relationships observed across all three services (mobile payments: r = .884, mobile savings: r = .856, mobile loans: r = .873, p < .05). Mobile payments facilitate timely transactions and new channels for mobile financial services, mobile savings promoting financial inclusion and fostering the habit of saving among individuals, while mobile loan offers assistance when there is a need for an emergency, finance for investment or business growth. Taken together, all of these services are critical in enhancing financial inclusion for farmers, helping with the farmers’ financial management, and improving their economic welfare. Lastly the research, emphasized the importance of the development of infrastructure and enhanced facilities for mobile money payments to enable the small scale farmers around Katente Village to attain financial inclusion. The study also suggests, there is a need to give more support and education regarding the mobile savings services for the achievement of financial inclusion. Lastly the study recommends satisfactory provision for the development of mobile loan services to meet the expectations of small scale farmers in Katente Village.